2022
DOI: 10.1101/2022.01.10.475623
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The genomic landscape of contemporary western Remote Oceanians

Abstract: The Vanuatu archipelago served as a gateway to Remote Oceania during one of the most extensive human migrations to uninhabited lands around 3,200 years ago. Ancient DNA studies suggest an initial settlement by East Asian-related peoples that was quickly followed by the arrival of Papuan-related populations, leading to a major population turnover. Yet, there is uncertainty over the population processes and the sociocultural factors that have shaped the genomic diversity of ni-Vanuatu, who present nowadays among… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…However, an initial ancient DNA study surprisingly found that individuals from Vanuatu and Tonga, dating to ~2.5-2.9 kya, possessed little or no Papuan-related ancestry (118). Subsequent studies showed that Papuan-related ancestry spread later, via mostly male-mediated, continuous migration (97,120,121). Other studies suggested back migrations from Polynesia (121) and native American ancestry that arrived in Polynesia before European contact (122), although the latter relies on analyses of modern samples and so far has not received any support from ancient DNA (123).…”
Section: Island Southeast Asia (Isea) and Oceaniamentioning
confidence: 99%
See 1 more Smart Citation
“…However, an initial ancient DNA study surprisingly found that individuals from Vanuatu and Tonga, dating to ~2.5-2.9 kya, possessed little or no Papuan-related ancestry (118). Subsequent studies showed that Papuan-related ancestry spread later, via mostly male-mediated, continuous migration (97,120,121). Other studies suggested back migrations from Polynesia (121) and native American ancestry that arrived in Polynesia before European contact (122), although the latter relies on analyses of modern samples and so far has not received any support from ancient DNA (123).…”
Section: Island Southeast Asia (Isea) and Oceaniamentioning
confidence: 99%
“…Subsequent studies showed that Papuan-related ancestry spread later, via mostly male-mediated, continuous migration (97,120,121). Other studies suggested back migrations from Polynesia (121) and native American ancestry that arrived in Polynesia before European contact (122), although the latter relies on analyses of modern samples and so far has not received any support from ancient DNA (123). Overall, instead of the stereotypical view that settlement of Remote Oceania involved one-time, "sweepstakes"-like successes amidst a sea of failures, genetic data confirm archaeological evidence for multiple dispersals and large-scale trade networks throughout Remote Oceania, including repeated contact with Near Oceania (124).…”
Section: Island Southeast Asia (Isea) and Oceaniamentioning
confidence: 99%
“…Beyond analytical modelling, population genetics studies have also measured ancestry-related assortative mating through the correlation of genetic ancestry proportions between mates Bryc et al (2010); Korunes et al (2022); Arauna et al (2022 ) . Non-random mating can also be monitored through deviations of the observed heterozygosity from Hardy-Weinberg equilibrium expected values Crow and Felsenstein (1968 ) .…”
Section: Introductionmentioning
confidence: 99%